(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Percutaneous vertebroplasty consists of the transcutaneous injection of bone cement (usually polymethylmethacrylate, PMMA) into the body of the damaged vertebra under fluoroscopic control. A needle is introduced through a posterior approach into the neural arch and vertebral pedicle. The cement fills cracks and voids, reinforcing the bone and restoring its strength.